2020
DOI: 10.1002/chem.202000857
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the 1,3‐Dipolar Cycloadditions of Allenes

Abstract: We have quantum chemically studied the reactivity, site‐, and regioselectivity of the 1,3‐dipolar cycloaddition between methyl azide and various allenes, including the archetypal allene propadiene, heteroallenes, and cyclic allenes, by using density functional theory (DFT). The 1,3‐dipolar cycloaddition reactivity of linear (hetero)allenes decreases as the number of heteroatoms in the allene increases, and formation of the 1,5‐adduct is, in all cases, favored over the 1,4‐adduct. Both effects find their origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…Finally, we examine cyclic allenes where the allenic moiety is constrained, thus perturbing the helical π-system. Cycloallenes are synthetically interesting compounds that, given their reduced symmetry due to the ring structure, exhibit helical MOs. ,, Most recently, Ramirez et al demonstrated that secondary orbital interactions due to the helical frontier MO topology are responsible for the endo selectivity in Diels–Alder reactions. Four molecular structures of simple cycloallenes are shown in the top of Figure , from left to right: 1,2-cyclo­hexadiene, 1,2-cyclo­heptadiene, 1,2-cyclo­octadiene, and 1,2-cyclo­nonadiene.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we examine cyclic allenes where the allenic moiety is constrained, thus perturbing the helical π-system. Cycloallenes are synthetically interesting compounds that, given their reduced symmetry due to the ring structure, exhibit helical MOs. ,, Most recently, Ramirez et al demonstrated that secondary orbital interactions due to the helical frontier MO topology are responsible for the endo selectivity in Diels–Alder reactions. Four molecular structures of simple cycloallenes are shown in the top of Figure , from left to right: 1,2-cyclo­hexadiene, 1,2-cyclo­heptadiene, 1,2-cyclo­octadiene, and 1,2-cyclo­nonadiene.…”
Section: Resultsmentioning
confidence: 99%
“…Thereafter, we showcase some recent advances of applying the ASM to various chemical problems, such as the competition between S N 2 and E2 reaction, 12 how metallylenes activate small molecules, 13 and the cycloaddition reactivity of cycloalkenes, cycloalkynes, and cycloallenes. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Cycloallenes are synthetically interesting compounds that, given their reduced symmetry due to the ring structure, exhibit helical MOs. 29,30,[71][72][73][74][75] Most recently, Ramirez et al 30 demonstrated that secondary orbital interactions due to the helical frontier MO topology are responsible for the endo selectivity in Diels-Alder reactions. Four molecular structures of simple cycloallenes are shown in the top of Figure 7, from left to right, 1,2cyclohexadiene, 1,2-cycloheptadiene, 1,2-cyclooctadiene and 1,2-cyclononadiene.…”
Section: Cycloallenesmentioning
confidence: 99%
“…29,30,[71][72][73][74][75] Most recently, Ramirez et al30 demonstrated that secondary orbital interactions due to the helical frontier MO topology are responsible for the endo selectivity in Diels-Alder reactions. Four molecular structures of simple cycloallenes are shown in the top of Figure7, from left to right, 1,2-…”
mentioning
confidence: 99%